2014
DOI: 10.1016/j.mib.2014.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Redox-driven regulation of microbial community morphogenesis

Abstract: During growth on surfaces, diverse microbial communities display topographies with captivating patterns. The quality and quantity of matrix excreted by resident cells play major roles in determining community architecture. Two current publications indicate that the cellular redox state and respiratory activity are important parameters affecting matrix output in the divergent bacteria Pseudomonas aeruginosa and Bacillus subtilis. These and related studies have identified regulatory proteins with the potential t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 51 publications
2
68
0
Order By: Relevance
“…Furthermore, the availability of electron acceptors, including oxygen, can drive structuring of biofilm morphology, as has been shown for Pseudomonas aeruginosa (35,36). Therefore, these findings expand the role that oxygen gradients can play in biofilm formation by highlighting an ability to modulate protein function.…”
Section: (31)supporting
confidence: 58%
“…Furthermore, the availability of electron acceptors, including oxygen, can drive structuring of biofilm morphology, as has been shown for Pseudomonas aeruginosa (35,36). Therefore, these findings expand the role that oxygen gradients can play in biofilm formation by highlighting an ability to modulate protein function.…”
Section: (31)supporting
confidence: 58%
“…In both of these systems, Pel has the effect of increasing O 2 availability, although the physical basis of this effect differs in the two regimes. In colonies, increased access to O 2 results from the increased colony surface area of a wrinkled morphology compared to a smooth one, which exposes a higher proportion of resident cells to the atmosphere (49). In pellicles, increased access to O 2 is achieved because the formation of the floating biofilm retains cells at the air-liquid interface in physical proximity to the atmosphere.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, when motile bacteria, such as Escherichia coli, adhere to a substratum (33,82,83), motility ceases, cell multiplication continues (84)(85)(86)(87), and early biofilm-related genes are upregulated, including those that encode additional adhesins (88)(89)(90). Although Karatan and Watnick (91) suggested that bacteria at this point can form either an adherent monolayer biofilm or a multilayer biofilm, the former is not sufficient to encompass some of the main characteristics of a complex biofilm, most notably the formation of ECM and a three-dimensional, controlled microenvironment that facilitates biofilm growth, nutrient acquisition, control of gas and pH, and cell-cell signaling (92)(93)(94)(95)(96)(97). It therefore may not be legitimate to consider an adhering cell monolayer lacking ECM a bona fide biofilm.…”
Section: Defining a C Albicans Biofilm: Lessons From Bacteriamentioning
confidence: 99%